Strategies and priorities for African agriculture: Economywide perspectives from country studies - Diao, Xinshen; Thurlow, James; Benin, Samuel; Fan, Shenggen (International Food Policy Research Institute, 2012)
This book examines the potential of agriculture to contribute to national growth and poverty reduction. It also evaluates the financial costs of accelerating agricultural growth. The analysis is based on ten country case studies that apply similar economywide approaches to linking growth, poverty, and investment. The findings indicate that, in most African countries, improving agriculture’s performance is essential to achieving pro-poor growth. They also point to export agriculture having high growth potential and becoming a prominent part of agricultural strategies. The research shows that broad-based growth will be difficult to achieve without expanding staple-foodcrop production and livestock production, since only they have the scale and linkages to poor households needed to reduce national poverty within a reasonable period of time. Finally, the case studies confirm the need for greater investment in agriculture. However, the efficiency of agricultural investments will have to improve if development targets are to remain attainable.